(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A sport (or sports) is often any organized sort of activity that involves competition. Sports competitions are performed to find the best athletes, teams, and feats in the sport, enhance athletic ability, and support physical culture and sports. sports competitions may be considered as an open conflict when the player or teams makes an effort to surpass the other player or teams in any sporting activity for which the competition is held. Anxiety is an unpleasant feeling that is hard to describe. It is significantly more challenging to accurately identify in performance. Sports anxiety is the term used to describe the worry and fear people experience when they see competitive situations as risky. (Rainer Martens, 1990). Competition anxiety is the behaviour of a player towards negative, emotional reactions to situations in which the competition may be lost, such as anxiety, tension, and fear. Anxiety is common in sports that affects a player’s performance when competing.